Effects of processing parameters of Roselle seed on its oil yield - Bamgboye, A. Isaac; Adejumo, Oyebola I. (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: The effect of the processing parameters of Roselle seed on its oil yield was investigated. The seeds were ground and classified into two particle sizes (fine and coarse) using ASAE Standard S319.3. The samples were conditioned by adding calculated amount of distilled water to different moisture levels from the initial moisture levels of 4.4% and 5.14% respectively, (fine, 4.4%, 6.4%, 8.4% and 10.4% and coarse samples 5.14%, 7.14%, 9.14% and 11.14%w.b.). The samples were heated at different temperatures of 80, 90, 100 and 110